Electronegative LDL from Rabbits Fed with Atherogenic Diet Is Highly Proinflammatory - Po-Yuan Chang; Jou-Hsiang Pai; Yu-Sheng Lai; Shao-Chun Lu (Hindawi Limited, 2019)
Electronegative low-density lipoprotein (LDL(-)) has been found in the plasma of familial hypercholesterolemia and acute myocardial infarction and has been implicated in atherosclerosis and cardiovascular disease. However, less is known about the involvement of LDL(-) in atherosclerosis-related inflammation. This study aims at investigating the inducibility of LDL(-) by atherogenic diet in rabbits and at exploring the proinflammatory potential of the diet-induced LDL(-) in macrophages. Rabbits were fed with an atherogenic diet; LDL was isolated from plasma by NaBr density gradient ultracentrifugation and was then resolved into nLDL and LDL(-) by anion-exchange chromatography. Isolated nLDL and LDL(-) were directly used or incubated with 10 μM CuSO4 for 24 h to produce copper- (Cu-) ox-nLDL and Cu-ox-LDL(-). The effects of these LDLs on inflammation were evaluated in THP-1-derived macrophages. Macrophages were treated with nLDL, LDL(-), and extensively oxidized LDL (ox-LDL), then the levels of interleukin- (IL-) 1β, IL-6, and tumor necrosis factor- (TNF-) α in a culture medium were determined by ELISA, and the levels of total and phosphorylated IκB, p65, p38, JNK, and ERK in cell lysates were determined by Western blotting. The LDL(-) induced significantly higher levels of IL-1β, IL-6, and TNF-α in the medium. The levels of phosphorylated/total IκB, p65, p38, JNK, and ERK were also upregulated by LDL(-). In contrast, nLDL, Cu-ox-nLDL, and Cu-ox-LDL(-) exhibited much less effect. Knockdown of lectin-type oxidized LDL receptor- (LOX-) 1 resulted in significant reduction in LDL(-)-induced IL-1β, IL-6, and TNF-α. In addition, these LDL(-) effects were also markedly attenuated by inhibition of NF-κB and ERK1/2. The data suggested that LDL(-) induced inflammation through LOX-1-, NF-κB-, and ERK1/2-dependent pathways. Taken together, our results show that rabbits fed with atherogenic diet produce a highly proinflammatory LDL(-) that is more potent in inducing inflammation than nLDL and extensively oxidize LDL in macrophages. The results thus provide a novel link between diet-induced hypercholesterolemia and inflammation.